Towards polarized training in tennis? Usefulness of combining technical and physiological assessments during a new incremental field test - Brechbuhl, C.; Girard, O.; Millet, G.; Schmitt, L. (Coaching and Sport Science Review, 2017)
Although tennis performance analysis underlines the relationship between physical and technical parameters, scientific or coaching approaches often neglect to develop these two aspects in the same training session. The effectiveness of combining physical and technical factors is reinforced by new results made available through the optimization of new technologies. Here, we discuss how the use of radar and ball machine may offer practical information to improve players` preparation concerning production of optimal ball velocity, ball accuracy and ball frequency.